BOARD GENDER DIVERSITY AND ITS IMPACT ON FIRM VALUE AND FINANCIAL RISK - yunia panjaitan (Universitas Mercu Buana, 2019)
One of the things that can be done to maximize firm value is by having a board of directors with diverse characteristics. Gender diversity in the firm’s board of directors can bring a positive impact to the firm. Females are generally more risk-averse than males, and this could lead to a lower risk that must be borne by the firm. This study is conducted to investigate the impact of Board Gender Diversity to firm’s value and financial risk. Using 51 manufacturing companies listed in the Indonesia Stock Exchange from year 2016 to 2017, data was analyzed with the multiple linear regression model for panel data. The findings suggest that the presence of female directors has a positive and significant effect to firm’s value, and a negative but not significant effect to firm’s financial risk